Kajian Terhadap Korelasi Kedisplinan Penyampaian LHKPN Anggota DPR RI Dengan Penegakan Kode Etik DPR RI - La Ode Risman (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The People's Representative Council of the Republic of Indonesia (DPR RI) is one of the highest state institutions in the Indonesian constitutional system and has the authority as stated in the provisions of Article 19, Article 20, Article 20A and Article 21 of the 1945 Constitution. The DPR RI is the enforcement agency for the DPR RI code of ethics as stated in the provisions of Article 119 of Law Number 17 of 2014 concerning MD3 Junto Law Number 2 of 2018 concerning MD3 Junto Law Number. 13 of 2019 concerning MD3. In the provisions of Article 1 paragraph (1) of Law no. 28 of 1999 concerning Administrators who are Clean and Free from Corruption, Collusion and Nepotism which states: State Administrators are officials who carry out the functions of the judiciary, executive, legislative and other officials. That LHKPN is a report in the form of a document containing personal data, assets, income, expenses and other data on the assets of state administrators. The regulations regarding State Officials' Wealth Reports (LHKPN) have been regulated in Law no. 28 of 1999 concerning the Administration of a State that is Clean and Free from Corruption, Collusion and Nepotism and apart from that, Law no. 30 of 2022 concerning Corruption Crimes. That in enforcing the DPR RI code of ethics against its members who commit violations, the Council Honorary Court (MKD) is the institution appointed to handle cases of reporting ethical violations committed by DPR members. Council Honorary Court (MKD) as stipulated in Article 119 paragraph (1) and (2) of Law Number 17 of 2014 concerning MD3 Junto Law Number 2 of 2018 concerning MD3 Junto Law Number. 13 of 2019 concerning MD3 .